"Nordic Aspirations": The Scottish discourse on the Nordic region - Berg, Laila (Nordlit, 2023)
This article explores the Scottish discourse on the Nordic region, that is, dominant conceptualisations of the Nordic region in contemporary Scotland in the context of the current Scottish nation-building project. Since the early 2000s, the Nordic region has received wide political attention and been presented as a viable and desirable role model for Scottish development by key political and social actors, including the Scottish Government and the Scottish National Party (SNP). This interest in the Nordic countries and the idea that they offer an alternative for Scotland which is line with dominant self-images of Scotland as egalitarian and social democratic has established itself as a central argument and aspect of the Scottish independence movement and the wider Scottish public debate. This article examines the historical development of the discourse on the Nordic region in Scotland, and its content by showing how the Nordic region is a multifaceted concept which intersects with Scottish nationalism and long-standing associations to the North. The Nordic region, in the Scottish context, is hence both a reality and a myth, a practical example and an idea. This dual quality is at the heart of the appeal and resilience of the Nordic region in contemporary Scotland, making the Nordic region Scotland’s main positive Other. Keywords The Nordic region, Scottish nationalism, the Other, discourse, conceptualisations of North